2011
DOI: 10.1063/1.3583453
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy and photoluminescence polarization in single InAlAs quantum dots

Abstract: We have investigated the optical anisotropy in individual self-assembled quantum dots. The linear polarization analysis of the positive trion photoluminescence reveals the effect of the strain-induced valence band mixing since the positive trion has the spin-paired holes and therefore exchange interaction has no influence. Meanwhile, the neutral exciton indicates the complex polarization states due to both the in-plain asymmetries of the dot shape and the strain distributions. The experimental and theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…45 This phenomenon has been found in GaN epilayers grown on foreign substrates suffering from in-plane uniaxial compressive stress [39][40][41][42] and also in self-assembled GaN quantum dots, which suffer from anisotropic stresses. 46,47 In order to verify if the present ZnO sample is strain-free (even locally), the strain anisotropy analysis is carried out with the aid of the high sensitivity of FWM to exciton polarizations: the FWM response is proportional to the fourth power of the transition oscillator strength jlj 2 . Indeed, this advantage plays an important role in detecting strain anisotropy even for the epilayers grown on isotropic substrates and bulk samples, in which only negligible strain anisotropy is expected.…”
Section: A Strain Anisotropy Analysismentioning
confidence: 99%
“…45 This phenomenon has been found in GaN epilayers grown on foreign substrates suffering from in-plane uniaxial compressive stress [39][40][41][42] and also in self-assembled GaN quantum dots, which suffer from anisotropic stresses. 46,47 In order to verify if the present ZnO sample is strain-free (even locally), the strain anisotropy analysis is carried out with the aid of the high sensitivity of FWM to exciton polarizations: the FWM response is proportional to the fourth power of the transition oscillator strength jlj 2 . Indeed, this advantage plays an important role in detecting strain anisotropy even for the epilayers grown on isotropic substrates and bulk samples, in which only negligible strain anisotropy is expected.…”
Section: A Strain Anisotropy Analysismentioning
confidence: 99%
“…Indeed, in II-VI CdTe/ZnTe 12,13 or III-V InAlAs/AlGaAs 14 QDs, VBM has been related to the strain anisotropy induced during growth process. In strain-free GaAs QDs grown by droplet epitaxy it has been shown that VBM exists due to the anisotropy of the confinement potential, 15 while in strained self-assembled InAs/GaAs QDs, VBM effects have been investigated in order to estimate the exciton spin relaxation time, 16 its influence on the exciton FSS, 17,18 or the hyperfine coupling.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, even in the case where there exists an observable polarization anisotropy, no distinct and reproducible directionality is observed, and the angle between the polarization components can differ from 90 , which is in good agreement with recent theoretical considerations and experimental reports. 24,31,32 AEI and VBM could well explain the observed small polarization of the single QD PL under the assumption of a much weaker electron-light hole transition compared to the electron-heavy hole transition. However, these contributions alone cannot explain the generally higher polarization of the lateral QDM PL.…”
Section: -4mentioning
confidence: 58%
“…[3][4][5] Strain-induced anisotropic exchange interaction (AEI) and valence-band mixing (VBM) might have an impact on the exciton FS, even for highly symmetric single QDs and QDMs, and are recently also discussed as possible sources for polarization anisotropy. 23,24 Especially the symmetry of QD structures and their confinement potentials, as well as their impact on the polarization of the related excitonic recombination, are important topics in current theoretical and experimental studies. 25,26 In this report, we investigate the polarization properties of single photons emitted from lateral InGaAs/GaAs QDMs manipulated by an electric field.…”
Section: Introductionmentioning
confidence: 99%